Master class with Leonidas Kavakos 2018 Leonidas Kavakos International Violin Masterclass & Chamber Music Workshop - Sibelius, Jean 1865-1957; Enesco, Georges 1881-1955 (DakApp, 2018)
Greek virtuoso violinist Leonidas Kavakos is one of today's most astonishing performers on his instrument: as put by Gramophone, there are few "violinists alive who can match Kavakos." Now in its seventh year, the Leonidas Kavakos International Violin Masterclass and Chamber Music Workshop is an annual master class at the Musical Horizons Conservatory in the violinist's native Athens. The three-day event attracts musicians and ensembles from around the world, and among the young and talented musicians participating this year is Luis María Suárez and Jonian-Ilias Kadesha. They work with Kavakos on the masterworks of the 20th-century violin repertoire: Sibelius's Violin Concerto and Enescu's Sonata for violin and piano. Photo © Chris Peppas